A review of biomarker and imaging monitoring to predict heart failure recovery - Yan, Crystal Lihong; Grazette, Luanda (Frontiers in Cardiovascular Medicine, 2023)
Heart failure is a clinical syndrome caused by structural cardiac abnormalities that lead to increased intracardiac pressures and decreased cardiac output. Following cardiovascular insult or direct myocardial injury, neurohormonal activation leads to hemodynamic changes and cardiac remodeling to preserve cardiac output. While initially adaptive, cardiac remodeling eventually leads to pathologic changes in cardiac structure that often compromise cardiac function. Reverse remodeling is the regression of abnormal cardiac chamber geometry and function after myocardial injury. In recent years, several classes of therapeutics have been associated with greater likelihood of reverse remodeling. Heart failure recovery and heart failure remission, terms encompassing the clinical correlates of reverse remodeling, have been associated with improved survival in patients with heart failure with reduced ejection. As such, identifying predictors of heart failure recovery can have important implications for guiding clinical practice and therapeutic innovation. This review addresses the role of biomarkers and imaging monitoring in predicting structural, functional, and clinical recovery in patients with acute and chronic heart failure.